Experimental investigation of the effects of different quaternary elements (Ti, V, Nb, Ga, and Hf) on the thermal and magnetic properties of CuAlNi shape memory alloy (Jun, 10.1557/s43578-022-00625-y, 2022) - Ozkul, Iskender; Karaduman, Oktay; Simsek, Telem; Simsek, Tuncay; Canbay, Canan Aksu; Ibrahim, Pshdar Ahmed; Arpa, Ipek Ak (Springer Heidelberg, 2022)
[Abstract Not Available]